Pengaruh Penambahan Hidroksiapatit Dan Waktu Pencelupan Terhadap Pelapisan Logam Stainless Steel 316L Dengan Metode Dip Coating - Nisa Mulya; Ahmad Fadli; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Stainless Steel 316L is metal that can be used as a bone plate, but it has low biocompatibility. To improve the biocompatibility Stainless Steel 316L coating hydroxyapatite is used. Thepurpose of this research was to study the effect of hydroxyapatite addition and dipping time on characterization of Stainless Steel 316L coated with HAp using Dip Coating Method. Metal with a size of 2x1x0,1 cm was dipped into a suspension containing HAp, sago starch and water that mixed with a rate of 150 rpm for 20 hours. The coating was done by varying the addition HAp 8, 10, 12 gr and dipping time of 2, 6, 10 seconds. The dipped Stainless Steel 316L was dried in oven at temperature 110 °C for 10 minutes. Coating HAp were sintered at temperature 800 °C for 1 hour. The research showed with increased HAp addition and dipping time the thickness of the coating HAp increased. With maximum shear strength obtained in this research is 0,24433 MPa.Keywords : Coating, Dip Coating, Hydroxyapatite and Stainless Steel 316L